The role of gender budgeting in implementing the obligation to provide resources to realise women's human rights in Africa - Killander, Magnus (University of Pretoria, 2017)
This thesis analyses the role of gender budgeting in implementing the obligation to provide resources to realise women's human rights in Africa. It uses the Southern African Development Community's (SADC) guidelines on gender budgeting adopted in 2014 (SADC guidelines) and the South African initiatives as case studies. In the first instance, the thesis considers the global, regional and sub-regional laws that make reference to the obligation to provide budgetary resources to realise women's human rights. Having established that African states have the obligation to provide budgetary resources to realise women's human rights, this thesis secondly presents gender budgeting as a means to do so. The thesis thirdly assesses the manner in which states can adopt gender budgeting to give effect to their women's human rights commitments. Learning from the shortcomings and the challenges of the SADC guidelines and the South African initiatives, this thesis proposes a framework on gender budgeting to be adopted by the African Union (AU). The study fourthly expands on the role of the AU and the SADC to ensure that African states adopt gender budgeting as a means to provide sufficient budgetary resources to realise women's human rights. Finally, the thesis has a chapter on conclusion and recommendations. This chapter elaborates on the key findings, provides for recommendations and makes suggestions for future research. The main recommendations of this thesis aim to ensure that African states adopt gender budgeting to implement their obligation to provide resources to realise women's human rights in their territory.